Development and in vitro evaluation of fast-dissolving oral films of ondansetron hydrochloride - Shohreh Alipour; Sahar Akbari; Fatemeh Ahmadi (Shiraz University of Medical Sciences, 2015)
Ondansetron hydrochloride, a selective 5-HT3 receptor blocker, is an effective antiemetic drug with oral bioavailability of %60 and half-life of 4-5 h. The present study was carried out to prepare fast dissolving films of ondansetron hydrochloride to increase patient compliance and improve efficacy of drug. Films were prepared by solvent casting method, using poly vinyl alcohol, poly vinyl pyrrolidone and konjacglucomannan as film formers and PEG400 as plasticizer. Natural and synthetic sweeteners were used for masking bitterness of drug. Satisfactory results were obtained from evaluation of physical characteristics of fast dissolving films of ondansetron hydrochloride including:  thickness: 37-39mm, surface pH: 6.77, folding endurance: up to 300 time and tensile strength: 35.75-50.93g/cm². Films were also subjected to an in vitro dissolution and release studies. In vitro drug release studies indicated 93-95% release in 5 min. Fast dissolving films of ondansetron could be a potential alternative for the currently marketed oral formulation, parenteral form and suppository with better patient compliance and higher bioavailability for the rapid control of emesis.